2022
DOI: 10.1038/s41467-022-35408-w
|View full text |Cite
|
Sign up to set email alerts
|

Charge polarity-dependent ion-insertion asymmetry during electrochemical doping of an ambipolar π-conjugated polymer

Abstract: Electrochemical doping is central to a host of important applications such as bio-sensing, neuromorphic computing and charge storage. However, the mechanisms that enable electrochemical dopability and the various parameters that control doping efficiencies are poorly understood. Here, employing complementary electrochemical and spectroelectrochemical measurements, we report a charge-polarity dependent ion insertion asymmetry in a diketopyrrolopyrrole-based ambipolar π-conjugated polymer. We argue that electros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Emerging flexible electronic technologies play a pivotal role in enhancing the portability and intelligence of electronic devices, including electronic skin, wearable devices, flexible displays, intelligent sensing, and brain‐machine interfaces. [ 1–11 ] The intrinsic flexibility of functional nano‐layers is crucial for ensuring the robust optoelectronic properties and long‐term deformation operation stability of flexible devices subjected to continuous strain. [ 3,5,12–18 ] Hence, semiconductor polymers (SPs) with inherent flexibility emerge as ideal materials for functional layers in flexible optoelectronic devices, given their potential for interchain entanglement and interpenetration.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging flexible electronic technologies play a pivotal role in enhancing the portability and intelligence of electronic devices, including electronic skin, wearable devices, flexible displays, intelligent sensing, and brain‐machine interfaces. [ 1–11 ] The intrinsic flexibility of functional nano‐layers is crucial for ensuring the robust optoelectronic properties and long‐term deformation operation stability of flexible devices subjected to continuous strain. [ 3,5,12–18 ] Hence, semiconductor polymers (SPs) with inherent flexibility emerge as ideal materials for functional layers in flexible optoelectronic devices, given their potential for interchain entanglement and interpenetration.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Indeed, CPs doped with molecular dopants show a similar level of carrier density, but their mobility is significantly lower than that of conductive ceramics. [22][23][24] Therefore, the poor electrical conductivity of the doped CPs is attributed to their low mobility rather than their charge-carrier density.…”
Section: Introductionmentioning
confidence: 99%
“…As for different electrolyte compositions, Flagg et al, Cendra et al and Samuel et al have demonstrated that, in accumulationmode OECTs, electrolytes composed of small ions with higher hydration spheres tend to promote higher swelling. [25,26,28] Despite this, even with superior swelling, these electrolytes result in devices with lower performance and sensitivity. These results, at first glance, may seem contrary to the approach to increase the hydrophilicity of the polymer backbone and, therefore, counterintuitive, since greater hydration of the film should facilitate the ionic penetration and hence increase the volumetric capacitance.…”
Section: Introductionmentioning
confidence: 99%